Facilities planning and design. - Garcia-Diaz, Alberto, ....-; Smith, James MacGregor, ....- (Upper Saddle River : Pearson, 2008)
This book takes a modern view of the field of facilities planning and design, along with a unified body of relevant knowledge.nbsp; Motivating and illustrating mathematical models wherever possible, the book explores facilities planning, capstone design, and even simulation modelling. A design project incorporates the theoretical aspects of facilities planning and design. The book also covers decision-support methodology and computerized procedures. nbsp; For industrial engineers, facilities managers, and plant managers.